Prarancangan Pabrik Asam Sulfat dari Sulfur dan Udara Kapasitas 325.000 ton/tahun - Tria Okti Anggraini, Devi, Tri Widayatno, S. T., M. Sc., Ph. D., Ir. Nur Hidayati, M.T., Ph.D (2016)
Sulfuric acid plant raw material with sulfur and air capacity of 325,000 tons/year it is planned to operate for 330 days/year. Products of sulfuric acid (98%) produced as much as 41,035.3535 kg/hour of need as much sulfur raw materials 13,218.9274 kg\/h and air dry as much as 84,905.6490 kg/h. Supporting utilities water supply include process amounted to 767,024.80 kg\/h, the electric needs of 650.157 kW obtained from the State electricity company (PLN) and supplied generator set as a backup. The planned factory is established in Banyuwangi, East Java by 2020 with a land area of 10,492 m2 and require employees of 282 people. Using sulfuric acid factory fixed capital is Rp. 700,551,445,143.45 and working capital amounting to Rp. 135,930,726,589. Economic analysis of the results against the factory obtained results Percent Return on Investment before tax amounting to 32.8% and after tax of 26.3%. Pay Out Time before tax amounted to 2.34 years and after of 2.76 years. Break Even Point (BEP) of 44,62%, Shut Down Point (SDP) by 21% and the Discounted Cash Flow (DCF) for 39,28 percent. From the above data then it can be inferred that the factory is profitable and viable. Keywords : sulphuric acid, kontak process, fixed bed